Structure of an Intranucleosomal DNA Loop That Senses DNA Damage during Transcription - Nadezhda S. Gerasimova; Olesya I. Volokh; Nikolay A. Pestov; Grigory A. Armeev; Mikhail P. Kirpichnikov; Alexey K. Shaytan; Olga S. Sokolova; Vasily M. Studitsky (Cells, 2022)
Transcription through chromatin by RNA polymerase II (Pol II) is accompanied by the formation of small intranucleosomal DNA loops containing the enzyme (i-loops) that are involved in survival of core histones on the DNA and arrest of Pol II during the transcription of damaged DNA. However, the structures of i-loops have not been determined. Here, the structures of the intermediates formed during transcription through a nucleosome containing intact or damaged DNA were studied using biochemical approaches and electron microscopy. After RNA polymerase reaches position +24 from the nucleosomal boundary, the enzyme can backtrack to position +20, where DNA behind the enzyme recoils on the surface of the histone octamer, forming an i-loop that locks Pol II in the arrested state. Since the i-loop is formed more efficiently in the presence of SSBs positioned behind the transcribing enzyme, the loop could play a role in the transcription-coupled repair of DNA damage hidden in the chromatin structure.